24‐segment sphericity index: a new technique to evaluate fetal cardiac diastolic shape. (4th May 2018) - DeVore, G. R.; Klas, B.; Satou, G.; Sklansky, M.
ABSTRACT: Objective: Because of parallel circulation in the fetus and the differential effect that various disease states may have on the shape of the right and left ventricles, this study was conducted to evaluate the sphericity index (SI) of 24 transverse segments distributed from the base to the apex of each of the ventricular chambers. Methods: Two hundred control fetuses were examined between 20 and 40 weeks of gestation. The displacement of the ventricular endocardium during the cardiac cycle was computed using offline speckle‐tracking software. From the ASCII output of the analysis, we analyzed 24 end‐diastolic transverse segments, distributed from the base to the apex of each ventricle, as well as the end‐diastolic mid‐basal–apical length. The SI was computed for each of the 24 segments by dividing the mid‐basal–apical length by the transverse length for each segment. Regression analysis was performed against biometric measurements and gestational age according to last menstrual period and ultrasound. Eight fetuses, in which the four‐chamber view appeared subjectively to demonstrate chamber disproportion, were evaluated as examples to demonstrate the utility of this technology. Results: The SI for each segment was independent of gestational age and fetal biometric measurements. The SI of the right ventricle was significantly ( P  < 0.001) lower than that of the left ventricle for segments 1–18, suggesting that the right ventricle was more globular in shape than was the left ventricle at the base, mid and a portion of the apical segments of the chamber. Fetuses with various cardiac structural abnormalities and abnormal fetal growth had abnormal SI values that reflected either a more globular or a more flattened ventricular chamber. Conclusion: Determination of SI for each of 24 segments of the fetal right and left ventricles provides a comprehensive method to examine the shape of the ventricular chambers. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked Comment: Ultrasound Obstet Gynecol 2018; 51: 571–572